Alterações bioquímicas e fisiológicas em cultivares de algodão (Gossypium hirsutum L.) quando submetidas ao estresse hídrico - Paula, Fernando Monteiro de (1985)
Seeds of two cotton cultivars (Deltapine smooth leaf and Mocó-9193) differing in drought resistance under dryland farming conditions were sown in polythilene trays containing vermiculite [...]